The association between body mass index (BMI) and neck circumference with sleep quality - Wuryan Dewi Miftahtyas Arum; Budiyanti Wiboworini; Ratna Kusumawati (Nexus Kedokteran Komunitas, 2014)
Backgrounds: Sleep disorders can affect on decreased concentration and academic achievement, sleepy while driving, risk behavior, depression, social interaction disorder, and bad health. Obesity is closely related to sleep-related breathing disorder that can affect on declining sleep quality as well. Body mass index (BMI) and neck circumference are simple screening to determine obesity. This research aims to know the association between BMI and neck circumference with sleep quality. Methods: This was an analytic observational research with cross sectional design in Buran Village, Tasikmadu, Karanganyar. Fifty six subjects 22-50 years of age were selected by using accidental sampling. BMI and neck circumference were obtained by anthropometric measurement. Sleep quality was obtained by PSQI questionnaire. Data were statistically analyzed using Spearman test and Mann-Whitney test. Results: The Spearman analysis indicated that there was no significant association between BMI and sleep quality (p = 0.070) as well as neck circumference and the sleep quality (p = 0.781). Mann Whitney analysis indicated that there was a significant association between psychological condition and sleep quality (p < 0.001). Conclusions: There are no significant associations between BMI and sleep quality as well as neck circumference and sleep quality. Psychological condition has significant correlation with sleep quality. Keywords: BMI, neck circumference, sleep quality